Analisis Inovasi dan Optimalisasi Supply Chain Management pada Sektor UMKM di Kawasan Lokal - Indrianto, Anggraeni Pratama; Nurahman, Ikhsan (Pascasarjana STIE Amkop Makassar, 2024)
This study aims to analyze the impact of supply chain management (SCM) practices on company performance, specifically focusing on the mediating role of supply chain performance within small and medium enterprises (SMEs) in the ceramic and pottery craft sector in Wedi, Klaten, Indonesia. Given the competitive pressures faced by SMEs, particularly in traditional craft industries, SCM practices are increasingly relevant for enhancing organizational performance and sustainability. The study employs a survey methodology, collecting quantitative data through structured questionnaires distributed to all 50 pottery and ceramic SMEs operating in the target area. To assess the relationships, path analysis was utilized, enabling a detailed examination of both direct and indirect influences of SCM practices on overall company performance. The SCM dimensions evaluated in this study include customer relationship management (CRM), supplier relationship management (SRM), goal congruence, and information sharing, each of which represents critical facets of SCM in this context. The results demonstrate that CRM, SRM, goal congruence, and information sharing each have a significant, positive effect on company performance. Additionally, these SCM practices positively influence supply chain performance individually. However, supply chain performance does not play a mediating role in the relationship between SCM practices and company performance, suggesting that SCM practices directly drive company outcomes without substantial mediation.